A polysaccharide of Dendrobium officinale ameliorates H2O2-induced apoptosis in H9c2 cardiomyocytes via PI3K/AKT and MAPK pathways - Zhang, Jing-yi; Guo, Ying; Si, Jin-ping; Sun, Xiao-bo; Sun, Gui-bo; Liu, Jing-jing (International journal of biological macromolecules, 2017)
•In this paper, we isolated and purified a homogeneous polysaccharide with molecular weight of 951.9kDa composed of glucose:galactose:mannose=2.13:1.34:1.00.•D. officinale polysaccharide may protest H9c2 cardiomyocytes apoptosis from H2O2-induced oxidative damage.•D. officinale polysaccharide could be applicable to therapeutics for myocardial ischemia/reperfusion injuries. Dendrobium officinale is one valuable traditional Chinese medicine, which has skyscraping medicinal value. Polysaccharide is the main active ingredient in D. officinale; its antioxidant activity is a hot research topic nowadays. Oxidative stress plays an important role in the pathological progress of a variety of cardiovascular disease, as one of key factors of cardiomyocyte apoptosis. This research adopts a model of H2O2 induction-H9c2 cardiomyocytes apoptosis, aiming to study the effect of Dendrobium officinale Polysaccharide (DOP-GY) for cardiomyocyte apoptosis caused by oxidative stress and its possible mechanism. Our results showed that pretreatment of DOP-GY (low dose: 6.25μg/mL, medium dose: 12.5μg/mL, high dose: 25μg/mL) followed by a 2h incubation with 200μM H2O2 elevated the survival rate, cutted the LDH leakage, reduced lipid peroxidation damage, improved the activity of the endogenous antioxidant enzymes. In addition, the pretreatment of DOP-GY significantly inhibited the production of ROS, declined of the mitochondrial membrane potential, down-regulated pro-apoptosis protein and up-regulated anti-apoptosis protein. The protective effect was correlated with the PI3K/Akt and MAPK signal pathway. Collectively, these observations suggest that DOY-GY has the potential to exert cardioprotective effects against H2O2-induced H9c2 cardiomyocyte apoptosis.